PARADIGMA DEPENDENCIA DALAM MEMAHAMI REALITAS KEMERDEKAAN BANGSA DAN NEGARA REPUBLIK INDONESIA PASCA REFORMASI 1998 - Ganjar Razuni (Universitas Nasional, 2016)
Indonesia’s political reform starting in 1998 has been a crucial path that poses problematic especially in terms of economic ideology and its road to development. This paper is an account that seeks to critically look into the negative move to ultra-liberal inclination of the reform with close collaboration with powerfully financial forces. The theories used are dependency theory and Feith & Castles’s concepts of five interwoven ideologies in Indonesia’s politics. It is the writer’s solution to the problem to endorse President Joko Widodo’s adoption of Sukarno’s Nawacita that calls for the path of self-reliant development and guarantees the re-invention of political philosophy of Pancasila.